Morgan Life Sciences - Flaumenhaft, Ben; Bagley, Constance E. ([London] : SAGE, 2016)
Morgan Life Sciences was a biotechnology firm headquartered in Waltham, Massachusetts. Initially, it focused on generic and over-the-counter medications, which it manufactured and distributed to drugstores and supermarket chains. Morgan completed a successful initial public offering in 1994, but by the late 1990s, the generics market had become increasingly competitive. Morgan steadily lost ground as its larger, low-cost competitors pushed prices relentlessly downward. This study explains how CEO Wendy Shaw set about transforming the fortunes of the company.
Originally Published in: Flaumenhaft, B., & Bagley, C. E. (2008). Morgan Life Sciences. 08-021. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Morgan Life Sciences (Firm); Organizational change -- Case studies; Business planning -- Case studies; Biotechnology industries -- Case studies